Performance prediction criteria based on yearling training cycle data for world-class athletes` tiny 1000-meter kayak teams: A case study - Dadelo, S.; Nekriošius, R.; Dadeliene, R. (Life, 2025)
This research aimed to identify optimal performance needs based on physiological tests of kayakers, revealing body adaptations and critical training periods within a yearly training cycle. It sought to develop performance selection protocols for teams and provide evidence-based strategies for future training.